Tannin Extraction from Bark of Cinnamomum burmannii and Its Application for use as Natural Dye and as Antioxidant - Widya Twiny Rizki; Winika Sri Wahyuni; Ririn Depita Sari; Siti Marwah Lestari; Rahmadevi Rahmadevi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
Cinnamon bark (Cinnamomum burmannii) contains tannins which have the potential to act as natural dyes. This research is to synthesize natural dye from cinnamon bark extract (Cinnamomum burmannii). The research was carried out by making cinnamon bark extract by comparing the amount of solvent by maceration using 96% ethanol, calculating the yield, tannin analysis, FTIR analysis, and stability test color. The comparison of the amount of cinnamon bark extraction solvent affected the resulting yield. Testing the tannin compound with 1% gelatin reagent in 10% NaCl showed a white precipitate and 1% FeCl3 reagent produced a greenish-brown color so the extract was positive for tannin, analysis FTIR ratio 1:10 for the presence of O-H, C-H, C=C, C-O groups, ratio 1:15 for the presence of O-H, C-H, C=C, C-O group. The color stability test of cinnamon bark extract is more stable than Rhodamine-B. Based on the extraction results, it was concluded that cinnamon bark extract can be used as an alternative to natural dye in cosmetic products.Keywords: Cinnamon Bark, Extract, FTIR Analysis, Natural dyes, Tannin